The Influence of Workload, Compensation and Work Motivation on Job Satisfaction at Al-Islam Hospital Bandung - Yulia Putri, Shofa; Gumilar, Dedi; Mubarok, Dadan Abdul Aziz (Dinasti International Journal of Management Science, 2024)
This study, titled "The Influence of Workload, Compensation, and Work Motivation on Job Satisfaction at Al-Islam Hospital Bandung," a to identify the elements that might affect employee work satisfaction, either partially or concurrently. The study will focus on three factors: Workload (X1), Compensation (X2), and Work Motivation (X3). The data will be collected through interviews and questionnaires. The test findings demonstrate that the Workload variable has a very negative and significant influence on job satisfaction, whereas compensation and work motivation have a very positive and significant influence, both partially and concurrently on job satisfaction among employees at Al-Islam Hospital Bandung. The findings of this report have implications that extend beyond academic interest. Organizations such as Al-Islam Hospital Bandung can benefit from a better understanding of the factors that influence employee job satisfaction. By addressing workload concerns and aligning compensation and motivation practices strategically, companies may provide a more pleasant work environment, resulting in better levels of employee satisfaction and well-being. This report can be used as a helpful tool for companies seeking to improve organizational performance by optimizing their human resource management strategies to promote employee happiness.